ANALISIS KEAMANAN SISTEM INFORMASI UNTUK MENGETAHUI KERENTANAN KEAMANAN SERVER DENGAN METODE PENETRATION TESTING EXECUTION STANDARD (PTES) PADA UNIVERSITAS VWX - Alvita Izana Kusumarini, (2021)
Server security is indispensable as well as prevention of information theft measures. This aspect is often ignored by some agencies, especially in universities because they already feel secure with the security conditions of the server network and consider the existing problems have not interfered with work activities by installing antivirus or firewall on the server. There are still many universities that still have not tightened the security of information on servers. Therefore, penetration testing is necessary to determine vulnerabilities in the server by using PTES (Penetration Testing Execution Standard) method to become standard in analyzing information security systems in finding security gaps in an agency in this case, namely employee data server at VWX University where in this study found vulnerabilities in the form of Cross Site Tracing (XST), Sensitive Data Exposure, Password Guessing, DDoS Attack, and Sniffing activities that can be done on the server for exploitation.